PTH-168 Organisation of an Acute upper Gastrointestinal Bleed Service in an average District General Hopsital. (4th June 2013) - Patani, O D; Duniak, N; Tan, C; Khalid, S
Abstract : Introduction: Acute Upper Gastrointestinal Bleed (AUGIB) continues to carry appreciable morbidity and mortality. Organisation and deliverance of emergency care incorporating therapeutic endoscopy is pivotal in the management of AUGIB. Recent British Society of Gastroenterology and NICE guidelines have recommended the introduction of a dedicated AUGIB service in institutions managing patients presenting with AUGIB. Since 2011 we set up a dedicated AUBIG service delivered by a team of gastroenterologists, surgeons and endoscopy support staff. The service currently runs 24 hrs a day and seven days a week. Methods: Through clinical coding, endoscopy and theatre database we identified all cases of AUGIB for the first year of the service. Data was collected retrospectively from patient case notes, endoscopy reporting system and emergency theatre records. Results: 77 cases of AUGIB were identified with gender distribution of 56% males and 44% females. The median age of presentation was 67 years (range 20–93 years). Most cases of AUGIB (71%) were acute admissions with the rest occurring among in-patients. A major improvement in the service is that all patients had at least one endoscopy during their presentation with most endoscopies (67%) performed within 24 hours or less and a further (26%) carried out 2–7 days. Endoscopies were performed by gastroenterologist (66%), surgeons (20%) and specialist registrar (14%). About a third (27%) had out of hours (OOH) emergency endoscopies and the remaining procedures were carried out in the dedicated in-patient lists. Majority (62%) of the OOH procedures were done at the weekends. A notable shortcoming was poor risk assessment (18%) at presentation although retrospective risk scoring revealed a median Rockall Score of 3 (range 1–5). At presentation only 8% of patients were admitted to the dedicated gastroenterology ward before the first endoscopy while the majority (52%) were managed initially on the acute medical wards and discharged or subsequently admitted to the gastroenterology ward. Conclusion: The introduction of a dedicated service has improved the management of AUGIB in our hospital serving a population of 325, 000 particularly during the OOH. The findings of this retrospective audit showed an AUGIB service collaborating medical gastroenterologists and surgeons is workable and sustainable in the setting of a district general hospital. To further improve the service a dedicated AUGIB clerking proforma incorporating Rockall risk score assessment is being considered. Disclosure of Interest: None Declared.